Inklusifitas Pemikiran Syaikh Nawawi al-Bantani - Maftuh, Rofik (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2018)
This paper tries to look at the views of Shaykh Nawawi al-Bantani in the commentary MarÄá¸¥ LabÄ«d, his work related to ahl al-Fatrah, the fate of the two parents of the Prophet Muhammad in the hereafter and his reliance on the fate of non-Muslims in the pre-Islamic and modern world The author discovers the interpretation of Shaykh Nawawi al-Bantani in al-Isra: 15 which classifies ahl al-Fatrah in three categories, namely the survivors, the unsaved, and those who have the possibility of surviving and not surviving. In these three categories, Shaykh Nawawi emphasizes the role of reason, thought effort, and forgiveness which influences a person including which category. The interpretation which according to the author is different from the others is that it leads to curiosity to see more deeply his thoughts, whether he is independent in thinking or influenced by other interpreters, or is related to socio-politics in his time. There are indications that his interpretation is relevant to the present, in the sense that there are isolated modern societies, not familiar with Islamic dawah but fulfilling the criteria in the category described by Shaykh Nawawi in his interpretation.